Empathy in adolescence: Parenting styles and individual factors of children and parents as predictors - Βάσιου, Αικατερίνη; Ανδρονικίδου, Ηλιάνα-Φανή; Κρασανάκη, Αναστασία; Τάνταρος, Σπυρίδων (Education Sciences, 2023)
Parenting nurturing practices are crucial to children’s emotional development. Empathy, as an important ability of children that implies a variety of positive social behaviors, seems to be related to parents' practices and it seems to change during adolescence. The present research investigated the relationship between parenting styles and adolescents’ empathy. 127 adolescents completed the Parenting Styles and Dimensions Questionnaire and the Basic Empathy Scale. The findings showed that the students’ cognitive empathy was positively related to the authoritative and permissive father as well as the authoritative mother. Moreover, authoritative mother and gender emerged as predictors of adolescents’ cognitive and emotional empathy. The results are important for understanding parents’ general contribution in emotional development during adolescence.